Rectal foreign body: case report and review of literature - Irpatgire, Ravindra; Sarda, Vikram; Kale, Dinkar (International Surgery Journal, 2016)
We present a case report of an unusual large foreign body in Rectum. Our patient presented with signs of intestinal obstruction following insertion of plastic oil bottle in the rectum for breaking fecal impaction. Patient was then evaluated and transanal retrieval of foreign body was carried out successfully.